Does religion matter? Public opinion on social issues in Costa Rica - Díaz-González, José Andrés (2021)
This article determines whether there is a relationship between religious beliefs and the perception of the Costa Rican population about various social problems and social behaviors. Data used for this purpose was obtained from a national public opinion survey, in which the opinions of Costa Rican population regarding various social problems and behaviors were collected. Such information was related, in most cases, to sexual and reproductive rights. It can be concluded that Costa Rican population behaves as predicted by the academic literature on this subject. People who profess an Evangelical Pentecostal belief or who indicate having a high religiosity, are more likely to adopt a non-favorable position towards sexual and reproductive rights. However, considering analyzed data, a relationship between the religious beliefs of the Costa Rican population and their perception regarding various social problems cannot be established.